FORMATION OF FEATURE SETS FOR SATELLITES CLASSIFICATION IN THE TASK OF ASSESSING THEIR CAPABILITIES - Bespalko , Iryna; Pekariev , Dmytro (Collection of scientific papers «ΛΌГOΣ», 2025)
Scientific and technological development has influenced the quantitative and qualitative composition of modern space systems, which is actively changing: the number of spacecrafts is increasing and their functionality are improving.